New types of sugar-containing raw materials for food production - E. I. Kuzmina; O. S. Egorova; D. R. Akbulatova; D. A. Sviridov; M. Yu. Ganin; A. A. Shilkin (Пищевые системы)
The global concept of conscious consumption and healthy life-style affects the development of the food industry. As a consequence, over the last several decades, a production of sugar substitutes has been increased, a search for and creation of new sweetening substances have been carried out. The paper presents a review of the domestic and foreign studies devoted to the use of sugar substitutes in various branches of the food industry. The information about new types of sugar substitutes from natural starch-containing raw materials and their properties is given. A possibility of replacing crystalline sugar with sugar substitutes in food production is described, their effect on the physico-chemical, sensory and organoleptic properties of foods and beverages is demonstrated. The development of the technologies facilitates an extension of the range of well-known and widely used high-calorie sugar substitutes from starch-containing raw materials, characterized by different carbohydrate composition and properties. It has been noted that out of quite a large number of sugar substitutes applied in the food industry abroad, glucose-fructose syrups (GFS) are among most promising. They are full-value sucrose substitutes and have several advantages. A proportion of GFS in the total volume of sugar syrup consumption is increasing worldwide every year. The main raw material for production of GFS in the USA is corn starch; in the CIS countries, starch obtained from wheat and potato is also used. Studies aimed to investigation and development of bioprocesses that ensure production of competitive enzymatic GFS and other sweetening syrups from alternative sources are gaining in importance. The information is presented about the development of the innovative technologies for production of sugar syrups from Jerusalem artichoke and chicory, agave, yacon, sorghum and rice. The results of the study of properties of these syrups and their effect on the physical and sensory, rheological and microstructural properties of products, in which technologies these syrups were used, are described. Due to the different carbohydrate composition, as well as physico-chemical properties (a degree of hygroscopicity, anti-crystallization properties, a level of sweetness, glycemic index and so on), sugar substitutes acquire increasing popularity among producers and consumers, and can be used in food and beverage manufacturing as a more technological replacement of crystalline sugar.